1988
DOI: 10.1002/1097-0142(19881201)62:11<2297::aid-cncr2820621106>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Activity of porphobilinogen deaminase in peripheral blood mononuclear cells of patients with metastatic cancer

Abstract: Porphobilinogen deaminase (PBGD), one of the enzymes in the pathway of heme synthesis, was found to be elevated in peripheral mononuclear cells of 60% of patients with epithelial tumors and metastatic spread, but only in 14% of patients with tumor and no evidence of metastases. The combination of both high lactic dehydrogenase and high PBGD afforded a sensitivity of 40%, but a specificity of 96% in diagnosing metastatic spread.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 9 publications
0
20
1
Order By: Relevance
“…The high accumulation of PpIX in tumour tissue is facilitated by the altered activity of some of the enzymes regulating the haem cycle. The porphobilinogen deaminase exhibits an increased and ferrochelatase a decreased activity in some malignant tissue (Rubino and Rasetti, 1966;Schoenfeld et al, 1988;Dailey and Smith, 1984;Leibovici et al, 1988). The abdominal wall muscle showed a much lower PpIX fluorescence intensity with a ratio of 0.33: 1 for the abdominal wall-liver and 0.42:1 for the abdominal wall -tumour.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high accumulation of PpIX in tumour tissue is facilitated by the altered activity of some of the enzymes regulating the haem cycle. The porphobilinogen deaminase exhibits an increased and ferrochelatase a decreased activity in some malignant tissue (Rubino and Rasetti, 1966;Schoenfeld et al, 1988;Dailey and Smith, 1984;Leibovici et al, 1988). The abdominal wall muscle showed a much lower PpIX fluorescence intensity with a ratio of 0.33: 1 for the abdominal wall-liver and 0.42:1 for the abdominal wall -tumour.…”
Section: Discussionmentioning
confidence: 99%
“…In the metabolic cycle of ALA, owing to variations in enzyme activity and bypassing of the feedback mechanism, an accumulation of the photodynamically very active protoporphyrin IX (PpIX) occurs in cells after excessive ALA administration locally, orally or intravenously. In particular, malignant tumour cells tend to synthesise more PpIX than non-malignant cells owing to a difference in the content of the enzymes regulating the haem cycle (Dailey and Smith, 1984;Leibovici et al, 1988). Experimental work and clinical trials using ALA-induced PpIX sensitisation have been performed (Malik and Lugaci, 1987;Kennedy et al, 1990;Kennedy and Pottier, 1992;Bedwell et al, 1992;van Hillegersberg et al, 1992a,b;Grant et al, 1993;Svanberg et al, 1994;Warloe et al, 1994).…”
mentioning
confidence: 99%
“…Accumulation is enhanced because of certain metabolic changes: an increased activity of the rate-limiting enzyme in the production of the heme group (porphobilinogen deaminase) 15 ; acceleration of the cell cycle in the tumor cells, which increases their capacity to take up ALA; and a higher density of mitochondria and a lower intracellular pH. 16 In addition, the changes in the stratum corneum of the epidermis in the plaques favor penetration of the photosensitizer into the skin.…”
Section: Mechanism Of Action Of Pdtmentioning
confidence: 99%
“…Kästle et al showed that WM451LU cells are more affected by ALA-PDT than non-tumorigenic keratinocytes (Kästle et al, 2011). The reason for this is elevated porphobilinogen deaminase activity and a significant decrease in ferrochelatase activity in cancer cells (Dailey et al, 1984;Kästle et al, 2011;Leibovici et al, 1988). What is more, PDT of melanoma with porphyrin and porphyrin derivatives is effective and well tolerated by patients (Szurko et al, 2003).…”
Section: Pdt In Melanoma Treatmentmentioning
confidence: 99%